PENGARUH SISTEM OLAH TANAH DAN PUPUK KANDANG AYAM TERHADAP SIFAT TANAH DAN PRODUKSI TANAMAN TERONG (Solanum Melongena L.) - Darnis, Afrianto; Sudjud, Suratman; Umasugi, Buhari; Hadun, Ramli; Melati, Rima; Samad, Sofyan (Universitas Khairun, 2025)
Carrying out the research using a tillage system (no tillage, minimum tillage, maximum tillage) and using chicken manure (no fertilizer, 20 tonnes/ha of chicken manure, 40 tonnes/ha of chicken manure). This research aims (a). to determine the interaction of the tillage system and chicken manure on soil properties and eggplant (Solanum melongena L.) production (b). To determine the effect of tillage systems on soil properties and eggplant (Solanum melongena L.) production (c). To determine the effect of chicken manure on soil properties and eggplant (Solanum melongena L.) production. carried out on Farmers' land in Guaemaadu Village, Jailolo District, West Halmahera Regency, which lasted for three months starting from October to December 2024. The height of the research location was 187 meters above sea level (m asl) with coordinates 01'03'23.55'N 127'27'40.26'E and the soil type was Inceptisol soil. Using a Factorial Randomized Block Design (RAK) with Two Factors. Observations were made on plant height, number of leaves, number of fruit, fruit weight, root length, particle density (BV), bulk density (BJ) and percent soil pore (% soil pore), soil pH and water rate (%KA). The results of the research obtained were that there was an interaction between the maximum tillage system and the dose of chicken manure of 40 tons/ha which had a real influence on root length and fruit weight. The maximum tillage system had a real influence on plant height, number of fruit, fruit weight and percent of soil pores. ton/ha has a real influence on plant height, number of fruit and fruit weight.